Evaluasi Implementasi Pendidikan Ekonomi pada Kurikulum 2013 (Studi Kasus pada SD Percobaan I Malang) - Rahma Sandi Prahara (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2017)
The Implementation of 2013 Curriculum in the education world, especially at the elementaryschool level has pros and cons that occurred in the community. The implementation of the 2013curriculum at elementary level has multidisciplinary and interdisciplinary approaches. Theproblem of K13 is not only on teacher readiness in knowledge transfer with this approaches butalso constrained on other stakeholders which consist of government, principals, institutions, andparents. Evaluation is a very important subsystem and is needed by every education systembecause it can be complementary or result of the education. This research is an evaluativeresearch using Countanance Stake model with qualitative descriptive approach. The research wasconducted at SD Percobaan 1 Malang. The results showed that (1) the planning phase was inaccordance with the standard; (2) Implementation phase was in accordance with the standard,however, it does not have the approach used in the Social Science lesson which did not use amutidisipliner approach; (3) assessment phase was in accordance with the standard; (4)Evaluation of social science lesson (Economics) grade 5 in terms of economic value inculcated inthe formal level are saving, buying and selling programs, bazaar program, and caring program. Ingeneral, the implementation of K13 in SD Percobaan 1 Malang runs in accordance with theapplicable standards, with this evaluation, the school are able to know the progress and retreat ofthe education quality and know the point of weakness and easy to find a way to change to bebetter.